Mechanochemical Control of Symmetry Breaking in the Caenorhabditis elegans Zygote - Gan, Wan Jun; Motegi, Fumio (Frontiers in Cell and Developmental Biology, 2021)
Cell polarity is the asymmetric organization of cellular components along defined axes. A key requirement for polarization is the ability of the cell to break symmetry and achieve a spatially biased organization. Despite different triggering cues in various systems, symmetry breaking (SB) usually relies on mechanochemical modulation of the actin cytoskeleton, which allows for advected movement and reorganization of cellular components. Here, the mechanisms underlying SB in C. elegans zygote, one of the most popular models to study cell polarity, are reviewed. A zygote initiates SB through the centrosome, which modulates mechanics of the cell cortex to establish advective flow of cortical proteins including the actin cytoskeleton and PAR proteins. The chemical signaling underlying centrosomal control of the Aurora A kinase-mediated cascade to convert the organization of the contractile actomyosin network from an apolar to polar state are also discussed.